EFFECTIVENESS OF THE CRIMINAL ACTION OF COLLECTIVE PROPERTY LAND CLAIMS - Malau, Boy Fernanda; Pratiwi, Siswantari; Mardani (JILPR Journal Indonesia Law and Policy Review, 2024)
The act of illegally grabbing land is an act that can be classified as a criminal act. Land grabbing will harm other parties, so the perpetrators can be prosecuted with criminal legal instruments. Land grabbing in reality in Indonesia is something that is difficult to avoid, especially in metropolitan areas, where empty land is increasingly difficult to find but more and more immigrants are arriving to risk their fate even though they do not have a clear place to live or relatives and this is what drives this. There are many cases of grabbing of state land and land controlled by individuals or companies. The formulation of the problem is: What is the ratio decidendi made by the judge in making considerations regarding the decision in the criminal case of land grabbing as contained in Decision Number 4/Pid.C/2021/PN.Sdr and Decision Number 05/Pid.C/2016/PN.BS? and What is the effectiveness of the land grabbing crime carried out by the perpetrators in Decision Number 4/Pid.C/2021/PN.Sdr and Decision Number 05/Pid.C/2016/PN.BS?. The research method used is normative legal research. The results of the research show that the Ratio Decidendi is made by the judge in making considerations regarding the decision in the case of criminal land grabbing as contained in Decision Number 4/Pid.C/2021/Pn.Sdr and Decision Number 05/Pid.C/2016/Pn.Bs In of the two decisions explained, it can be concluded that these are the main points or reasons that form the basis of the judge's ratio decidendi decision in deciding the case and the effectiveness of the crime of land grabbing carried out by the perpetrators, as explained in the Both decisions show great attention to the protection of the rights of legal land owners. In analyzing the effectiveness of criminal land grabbing, it was found that the legal system must continue to develop to overcome existing challenges and weaknesses.